Insights into the Efficacy of GLP-1 Agonists and Dual Agonists: Semaglutide and Tirzepatide in Obesity and Type 2 Diabetes - Laura Opalska; Adrianna Muciek; Martyna Mocarska; Anna Orłowska; Katarzyna Strakowska; Anna Maryńczak; Jan Mencel; Nicole Nitschke (Quality in Sport)
The increasing global prevalence of obesity and type 2 diabetes (T2D) has prompted significant advancements in pharmacological treatments, with glucagon-like peptide-1 (GLP-1) receptor agonists and dual agonists representing key innovations. Semaglutide, a GLP-1 receptor agonist, and tirzepatide, a novel dual agonist targeting both GLP-1 and glucose-dependent insulinotropic peptide (GIP) receptors, have shown remarkable efficacy in improving glycemic control and promoting weight loss.